Advanced PEDOT thermoelectric materials - Jiang, Fengxing; Liu, Congcong; Xu, Jingkun (Woodhead Publishing series in electronic and optical materials., 2022)
PEDOT is currently the most widely used polymeric material in research and development. Over the past 10 years, PEDOT has been investigated for potential organic thermoelectric applications because of its superior thermoelectric and mechanical properties compared with other conductive polymers. However, many challenges remain to be solved before it is translated into key technologies. Advanced PEDOT Thermoelectric Materials summarizes current progress and the challenges of PEDOT thermoelectric materials, while clarifying directions for future development. This book provides a comprehensive overview of chemical, physical, and technical information about this organic thermoelectric polymer. The authors also give details about the theoretical basis of PEDOT, including preparation and characterization, and its development as a high-performance thermoelectric material.